Photodegradation of ibuprofen using CeO2 nanostructured materials: Reaction kinetics, modeling, and thermodynamics. Issue 3 (June 2022) - Gallucci, Noemi; Hmoudah, Maryam; Martinez, Eugenie; El-Qanni, Amjad; Di Serio, Martino; Paduano, Luigi; Vitiello, Giuseppe; Russo, Vincenzo
Abstract: Ibuprofen is one the most used non-steroidal anti-inflammatory drug, which is considered an emerging pollutant that may contaminate surface and underground water. Photodegradation using nanomaterials is one of the most sustainable and cheap technologies that can be used in water purification. In this study, the photodegradation efficiency of in-house prepared ceria (CeO2 ) nanostructured materials towards ibuprofen was assessed under UV irradiation. CeO2 nanoparticles (NPs) were prepared through wet-chemical synthesis and characterized by several techniques. The photodegradation activity of the synthesized CeO2 -NPs was compared to the commercial Aeroxide TiO2 -P25. Small crystalline CeO2 -NPs were obtained with about 15 nm particle size, band-gap of 3.1 eV with irregular morphology. The surface area of CeO2 -NPs was estimated to be 76 ± 5 m 2 /g. Dynamic light scattering analysis revealed that these nanoparticles have a strong tendency to self-aggregate and to form clusters in aqueous suspension. The results showed a slightly better performance of Aeroxide TiO2 -P25 compared to CeO2 -NPs. On the other hand, five reusability tests confirmed the stability of CeO2 -NPs in the reaction conditions, without any significant effect on their photodegradation activity. The goodness of the kinetic modeling of the experimental data was proven through the estimated kinetic parameters, together with the statistical information. The temperature effect confirmed that the higher the temperature, the greater the dissociation rate. Thus, there is a direct relationship between temperature, reaction rate, and the activation energy for each reaction. Furthermore, the thermodynamic parameters, namely: changes in Gibbs free energy ( ∆ G ° ), enthalpy ( ∆ H ° ), and entropy ( ∆ S ° ) have been reported revealing the efficient photodegradation performance of CeO2 -NPs. Graphical Abstract: ga1 Highlights: Ibuprofen is considered an emerging water pollutant. CeO2 nanoparticles (NPs) were prepared through wet-chemical synthesis. CeO2 -NPs were characterized by XRD, XPS, TEM, DLS, and UV-Vis DRS techniques. The photodegradation activity of CeO2 -NPs was compared to Aeroxide TiO2 -P25. Reusability tests confirmed the stability and the sustainability of CeO2 -NPs.